Strategi Eksklusi pada Film Dokumenter The Mahuzes Karya Watchdoc Documentary: Kajian Critical Discourse Analysis Theo Van Leeuwen - Irma Suryani; Kamiyatein Kamiyatein; Julisah Izar (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
This study aims to examine the construction of the exclusion strategy used by Watchdoc in The Mahuzes documenter film. The data used in this research is the text of the speech in the film obtained from the transcripts.The method used is a descriptive qualitative method with Van Leeuwen approach to Critical Discourse Analysis (CDA). The result showed that Watchdoc used passivation and nominalization strategies to eliminating social actors in the film trough narrative descriptions, journalists speech, and adat community stories. Watchdoc uses the form of passivation dijadikan, dibongkar, dibersihkan and nominalization perebutan, penggusuran, andpembongkaran to criticize government policies and corporate industrial activities in Papua. By eliminating the actors in the film, the audience will think critically about the people involved in events and circumstances that are destrimental to adat community in Papua.